The evolution of environmental extremism in the United States - Preskitt Muir, Danielle Marie (Kansas State University, 2023)
The threat posed by environmental extremism is a product of the way in which the environment is presented to the public as well as the government’s response. Through a comparative analysis of case studies, this dissertation argues that the US government’s history of using repression in the form of decentralization strategies and rhetorical delegitimation has failed to stop eco-radicalism. A social, cultural, and historical analysis of the selected environmental movements’ histories identifies the root cause of the transformation while warning that engagement has proven a superior tactic to repression in dealing with eco-radicals. ELF and ALF’s decentralized nature, leadership structure, and the US government’s failed repression strategies have facilitated the organizations’ increased level of violence. On the other hand, Greenpeace’s cohesive structure as well as their sense of collaboration and consensus shaped its relationship with the government as well as its decision to rely on consistently peaceful tactics. The concepts of transparency, consensus, and cohesion within Greenpeace and its interactions with the US government contributed to its longevity as well. While these organizations share common concerns, their approaches and philosophies differ greatly. In response to the US governments’ actions, ELF and ALF turned toward violence in frustration while Greenpeace leaned further into lobbying and collaboration to promote lasting change. This dissertation goes beyond the current literature by seeking to answer the following research question: How does the government response trigger a change in tactics from nonviolent to violent in environmental groups? Rational choice theory provides insight into the decision-making process of the organization in response to the government. This dissertation further warns policymakers against relying primarily on repression in dealing with eco-radicals because it has proven counter-productive in the past.
Keywords: Eco-radicals; Environmental; Extremism; Repression